Progress in Science, Progress in Society - Tressaud, Alain; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book addresses current societal debates around the globe. Written by respected researchers from France, Germany, Belgium, Denmark, Spain, Portugal and Italy, the chapters are based on presentations given at a conference organized by the European Academy of Sciences, in partnership with the Royal Academy of Belgium and French Academy of Sciences, in Brussels (Belgium) in November 2016.  The book approaches science and society from a perspective of progress. Does progress in science ultimately translate into progress in society? How can we ensure that scientific progress becomes both materially and intellectually beneficial for society, including people who are far away from or socially excluded from it? Progress is a common feature of science and of human societies. There is no doubt that one of the driving forces of the material and intellectual progress of mankind has been science and technology. However, these are not the only forces acting on human history, so that the role of science and technology is not always fully recognized and sometimes even rejected. The various chapters of this book cover many aspects of these issues, arriving at valuable new insights.
Introductory presentation to Progress in Science, Progress in Society.-Science and Social Communication -- Contentious Research: How to Respond to the Credibility Crisis of Science -- A more inclusive science education : La Main à la pâte and beyond -- The contribution of Social Sciences and the Humanities to research addressing societal challenges -- Resistances to agricultural biotechnologies, agronomy and environment -- New perspectives in genetic therapies -- From cryptography as a science to a tool for an open and trusted society -- Technological innovation as a factor of penetration of science in society -- Law, a response to risks of technology application -- Research and the Industry of the Future -- Where science fiction meets reality -- Two-dimensional oxides: new structures, new functions and new materials -- How does Artificial Intelligence work with Remote Sensing Technologies for multiscale environmental change detection?
Keywords: Chemistry; Social sciences; Humanities; Agriculture; Chemistry; Humanities and Social Sciences; Agriculture